Nutrition and physical activity behaviors in 16-18 -year-old adolescents in Tirana - Kosta, Orkida; Kosta, Ortensia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Being overweight or obese is a sign of nutritional issues in teenagers. An imbalance between adolescent physical activity and dietary consumption contributes to overweight. The purpose of this study was to ascertain the effects of dietary variations and physical activity on adolescents’ nutritional status. This particular research employed a cross-sectional design framework. The study involved 510 adolescents aged 16 to 19 years who were in a school in Tirana. A questionnaire intended to assess health-promoting activities was filled out by adolescents and was based on two subscales of the HPLP II. The ANOVA test was used to analyze the statistical data. The findings indicated a statistically significant difference in nutritional intake between adolescents with normal nutritional status and those with a higher nutritional status, with a p-value of (p<0.05); however, statistically significant difference was observed in nutritional intake and physical activity levels between the two groups of adolescents, as indicated by p-value of (p>0.05). There is a difference in consumption, and we can deduce variations in dietary consumption and physical activity based on teenagers’ nutritional status. The nutritional status and dietary nutrient intake of adolescents should be monitored from an early age. It is important to maintain regular exercise to prevent nutritional issues that may lead to non-communicable diseases.